Microbiological Quality of Vannamei Shrimp Pond Waters in Rupat Island, Bengkalis District, Riau. Issue 1 (1st December 2022) - Nursyirwani, N; Mardalisa, M; Batubara, U M; Nurhayati, N; Putri, R F
Abstract: The presence of pathogenic bacteria in shrimp culture water could influence the shrimp growth and production. This research aimed to quantify total coliform, Escherichia coli and total Vibrio in pond water of Vannamei shrimp ( Litopenaeus vannamei ) culture in Rupat Island. Water samples from inlet water (IW), water from three ponds (PW2, PW3, PW6) and outlet water (OW) were collected for the quantification of total coliform and Escherichia coli by the MPN technique and total Vibrio count on TCBS agar. Coliforms was found in all water samples, the lowest count was in inlet water sample (20 MPN/100 mL), and the highest was contained in outlet water (>2400 MPN/100 mL), however E. coli was not detected in all water samples. Meanwhile, the lowest total Vibrio count was found in PW3 (6.35 × 10 3 ), and the highest was in the PW6 (3.10 × 10 5 ). In addition to the microbiological quality, some water quality parameters were also observed, those were water temperature in the range of 27.5- 29.4°C, salinity of 18.7-21.5 ppt, pH of 7.17-7.89, DO of 1.3-7.6 mg/L, NH3 content of 0.96-1.26 mg/L and DOM of 26.2–27.6 mg/L. The data indicated that pathogenic bacteria were present in all pond waters which should be decreased for the safety shrimp production.